A different kind of ethnography : imaginative practices and creative methodologies - Culhane, Dara; Elliott, Denielle (University of Toronto press, 2017)
"Produced by members of the Centre for Imaginative Ethnography, this collection introduces the idea of an imaginative and creative approach to anthropological inquiry, one that is collaborative, open-ended, embodied, affective, and experimental. Rather than structuring the book around traditional methods like interviewing, participant observation, and documentary research, the authors organize their thoughts around different methodologies--sensing, walking, writing, performing, and recording. As well, innovative, practical exercises are included that allow ethnographers to not just 'talk the talk', but also 'walk the walk' so they can deepen, complicate, and extend ethnographic inquiry. A list of additional resources at the end of each chapter provide rich support for those who want to pursue more imaginative and creative methodologies."--